Role of media in the pharmaceutical processing of Krishna Vajra Abhraka - A Fourier Transmission Infrared Spectroscopy study (FTIR) - Rai P.; Kumar N.; Singh R.S. (My University, 2025)
Krishna Vajra Abhraka (Biotite) is an important and potent mineral used as medicine for different therapeutic purposes in the Ayurveda since long back. Abhraka is not used directly in the native form as founds in the ore. It is subjected to different pharmaceutical processing like Shodhana and Marana (incineration) described in Ayurvedic texts that converts into therapeutically important form. These processes lead to physico-chemical changes in the Abhraka which makes therapeutically suitable form. In this paper an attempt has been made to find out the chemical changes takes place in the Abhraka after process of Shodhana from different Media by Fourier transmission Infrared Spectroscopy Study (FTIR).